Mechanical and biocompatibility analyses of metabiomaterials cobalt chrome molybdenum manufactured by selective laser melting for load bearing implant - Siti Rohaida, Mohamed (2017)
Cobalt chrome molybdenum (Co-Cr-Mo) alloy has been routinely used in load bearing implants due to the biocompatibility, excellent strength and toughness, and high resistance to wear and corrosion. However, the implants possess high stiffness (220 GPa) compare to human bone (1-30 GPa). The difference in the stiffness caused stresses to be transferred predominantly through the implant, known as stress shielding phenomenon, where is the main reason for revision surgeries. Despite of advantages of additive manufacturing (AM) in producing complex shape parts, the quality of the produced components such as surface finish, accuracy, density, mechanical properties and biocompatibility status are scarce. Thus, this research study presents the designs of metabiomaterials with controlled geometrical for the possible way to tailor the stiffness and provide the space for biological response of implant part made by Co-Cr-Mo alloys powder manufactured through selective laser melting (SLM), one of the AM techniques. The metabiomaterials unit cell of square and diamond type with varied geometrical unit cell length, Lcell ranged from 1.5 mm to 2.5 mm and strut size, Φs ranged from 0.4 mm to 0.6 mm generated through SolidWorks software and then manufactured with default manufacturing process parameters. The relative density and dimensional accuracy tolerance were calculated while morphology and manufacturability were evaluated. The mechanical and biocompatibility properties are determined through compression test with load 100 kN and in vitro MTT assay where the samples are grouping into two groups based on sterilisation methods of gamma irradiation and autoclave techniques. As the results, the metabiomaterials exhibit porosity ranged from 44.8 to 88.1% and pore size range from 0.9 to 2.1 mm. The metabiomaterials resulted higher relative densities ranged from 84.7 to 97.7% influenced by higher energy density during manufacturing process. Morphology evaluation revealed partially melted powder bonded to the strut core while the manufacturability for metabiomaterials met a good geometrical agreement with original CAD models. The overhang phenomenon, as stresses tend to dross formation occurred at unsupported region with tolerance less 1% and the shrinkage on height feature dimension of the square unit cell was observed. The stiffness of metabiomaterials resulted in properties of cancellous (spongy) bone ranged from 0.45 to 8.75 GPa and the compression strength ranged from 10.77 to 245.03 MPa. From MTT absorbance assay, the samples SL25T04 and DL25T04 (pore size 2.1 mm and 1.7 mm) resulted the highest absorbancy of 0.6 and 0.45 OD which shown the highest cells viable in the samples. MTT assay demonstrated that components produced by SLM are not harmful to the cells and no proof to cells death. The outputs from this research are significant to be used as the groundwork for further development of metabiomaterials Co-Cr-Mo produced by SLM for load bearing implants. Consideration on further study on fatigue analysis, biocompatibility in vivo (in animal), amount of metal-ion released and physical evaluation on varied manufacturing process parameters are suggested for future works.